1990
DOI: 10.1111/j.1469-7610.1990.tb01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Competencies Reported by Parents of Australian and American Children

Abstract: We compared problems and competencies reported for 2600 randomly selected nonreferred children in Sydney and the U.S.A. Sydney children scored significantly higher on 82 problem items, with a mean total problem score of 31.6 versus 20.1 for the U.S.A. Nevertheless, item scores correlated 0.92 between countries, most differences between competence scores were small, and patterns were similar for sex, age, socioeconomic status, and internalizing versus externalizing problems. Although higher clinical cutoffs may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
2

Year Published

1994
1994
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 20 publications
5
34
2
Order By: Relevance
“…Gender differences in this study were consistent with those found in previous studies of Chinese children (Ekblad, 1989;Xin et al, 1992), with analogous differences between boys and girls on other measures. They are also consistent with gender differences found in several other countries (Achenbach, Hensley, Phares, & Grayson, 1990).…”
Section: Gender Differencessupporting
confidence: 90%
See 1 more Smart Citation
“…Gender differences in this study were consistent with those found in previous studies of Chinese children (Ekblad, 1989;Xin et al, 1992), with analogous differences between boys and girls on other measures. They are also consistent with gender differences found in several other countries (Achenbach, Hensley, Phares, & Grayson, 1990).…”
Section: Gender Differencessupporting
confidence: 90%
“…In a comparison between 2,600 Australian and American 4-to 16-year-olds, Australian children obtained higher CBCL Total Problem scores than American children (31.6 versus 20.1), a medium effect accounting for 11% of the variance (Achenbach, Hensley, Phares, & Grayson, 1990). In a comparison between parent reports on 1,842 matched French and American children, American children tended to receive higher competence scores, while French children tended to receive higher problem scores (Stanger, Fombonne, & Achenbach, 1994).…”
mentioning
confidence: 93%
“…Comparing with the U.S. children, Puerto Rican, Australian, and Thai parents have reported higher total problem scores using the Child Behavior Checklist (Achenbach, Bird, et al, 1990;Achenbach, Hensley, Phares, & Grayson, 1990;Weisz et al, 1987). While the actual prevalence rates of various disorders may differ from one place to another, it is plausible that some of the variations reflect different thresholds of recognition and reporting of particular problems.…”
Section: Discussionmentioning
confidence: 95%
“…Puerto Rico) have documented interesting, albeit modest, differences in the frequency of behavioral and emotional problems that may reflect the contribution of cultural influences (Achenbach, Hensley, Phares, & Grayson, 1990;Achenbach, Verhulst, Baron, & Althaus, 1987;Achenbach, Verhulst, Edelbrock, Baron, & Akkerhuis, 1987;Brandenburg, Friedman, & Silver, 1990;Lambert, Weisz, & Knight, 1989;Weisz, Suwanlert, Chaiyasit, & Walter, 1987;Weisz et al, 1989). This study was undertaken to examine the feasibility of utilizing the Child Behavior Checklist (CBCL) in a genetic-epidemiologic project in the greater Moscow area.…”
mentioning
confidence: 98%